Perancangan Instalasi Penerangan Pada Gedung Laboratorium Dan Perkuliahan Terpadu Universitas Borneo Tarakan - Aprizulkifli Aprizulkifli; Sugeng Riyanto (Elektrika Borneo, 2021)
The design of the lighting installation in the Integrated Lecture and Laboratory Building of the University of Borneo Tarakan. Generates a total power of about 31,048 KW with MCCB capacity on the main panel of 150 A. In this building is divided into 3 floors (1, 2 and Top Floor). Each group has its respective power (18,400, 12,328 and 320 Watt) and the nominal currents of each group are (35, 35, and 2 Ampere). The resulting stress loss is 0.4%